INTERMODAL TRANSPORTATION: COMPOSITION OPTIONS AND THE IMPORTANCE OF MARITIME TRANSPORT - Drozhzhyn, O. L. (Systems and Technologies, 2025)
The paper examines the definition of “door-to-door” in relation to intermodal transportation and considers its author’s interpretations. The definition of intermodal transportation as a type of multimodal transportation is considered, its features are established in accordance with Ukrainian legislation. The starting and ending points that form intermodal transportation are identified and the conditions of intermodality are listed. Identification of the beginning and end of intermodal transportation is important in terms of establishing the locations where the intermodal transportation operator assumes and disclaims liability for the cargo. To prove the groundlessness of the statements about door-to-door delivery as a sign of intermodal transportation, the author presents technological maps of intermodal delivery under CIF and FOB contracts, which may be intermodal, but do not connect the door of the sender’s warehouse with the door of the consignee. These examples illustrate the boundaries of intermodal transportation under the responsibility of the operator and areas where transportation takes place outside the operator’s boundaries and is not the responsibility of the operator. Such a distinction establishes different statuses for these two carriers and, as a result, different levels of liability for loss and damage, and delay of cargo. The study is based on the definition of inter-modal transportation in accordance with national legislation, as well as the author’s formulations of this definition provided by Ukrainian and foreign scholars in their publications. As a result, the following conclusions have been established: the key factor in transforming conventional segmented transportation into intermodal transportation is not just the use of several modes of transport, but rather their interaction, which provides a connection between land and sea sections of the route. Therefore, the participation of maritime transport is an integral part of the transport support for international trade. Intermodal transportation does not necessarily cover the entire route “from the sender’s door to the recipient’s door”. – It may begin or end at other points along the route in accordance with the selected basic terms of delivery, provided that certain “intermodality” features are main-tained. Under any conditions of supply of goods, each intermodal transportation is managed by a single intermodal transport operator, which issues a through transport document that ensures communication between the consignor and the consignee.